2022
DOI: 10.1186/s12931-022-01994-y
|View full text |Cite
|
Sign up to set email alerts
|

One-year pulmonary impairment after severe COVID-19: a prospective, multicenter follow-up study

Abstract: Background Long-term pulmonary sequelae following hospitalization for SARS-CoV-2 pneumonia is largely unclear. The aim of this study was to identify and characterise pulmonary sequelae caused by SARS-CoV-2 pneumonia at 12-month from discharge. Methods In this multicentre, prospective, observational study, patients hospitalised for SARS-CoV-2 pneumonia and without prior diagnosis of structural lung diseases were stratified by maximum ventilatory sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
57
2
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 26 publications
10
57
2
8
Order By: Relevance
“…Given the design of our study, the patients were not systematically rescheduled for long-term reassessment, which represents a major limitation. Interestingly, two recent studies decribed 1-year follow-up features of severe hospitalized COVID-19 patients, showing frequent persistent fatigue, dyspnea, and quality of life impairment [ 36 ] and also DLCO alteration and persistent interstitial lung abnormalities especially in older patients requiring ventilatory support [ 37 ]. Our study is also limited by its single-center design, the potential selection bias of patients who consented to a 3-month assessment, the relatively low number of patients, the absence of pre-COVID-19 data regarding respiratory symptoms, pulmonary function, CT scan, sarcopenia and psychological symptoms, and the absence of systematic assessment of pulmonary arterial hypertension by echography.…”
Section: Discussionmentioning
confidence: 99%
“…Given the design of our study, the patients were not systematically rescheduled for long-term reassessment, which represents a major limitation. Interestingly, two recent studies decribed 1-year follow-up features of severe hospitalized COVID-19 patients, showing frequent persistent fatigue, dyspnea, and quality of life impairment [ 36 ] and also DLCO alteration and persistent interstitial lung abnormalities especially in older patients requiring ventilatory support [ 37 ]. Our study is also limited by its single-center design, the potential selection bias of patients who consented to a 3-month assessment, the relatively low number of patients, the absence of pre-COVID-19 data regarding respiratory symptoms, pulmonary function, CT scan, sarcopenia and psychological symptoms, and the absence of systematic assessment of pulmonary arterial hypertension by echography.…”
Section: Discussionmentioning
confidence: 99%
“…So wurden in einer Studie 12 Monate nach einer COVID-19-Erkrankung mit Hospitalisierung nur bei 1 % der Patienten fibrotische Folgeerscheinungen (im Sinne von "honeycombing") in der hochauflösenden Computertomographie (HR-CT) gefunden. In den meisten Fällen dieser Studie (66 % der Patienten) wurden nichtfibrotische Veränderungen mit eingeschränkter anatomischer Ausdehnung beobachtet [11]. Ähnliche Befunde ergaben sich im 2-Jahres-Verlauf nach COVID-19 [19].…”
Section: Radiologische Veränderungenunclassified
“…Auch andere Studien zeigten eine leichte Einschränkung der TLC und DLCO nach mildem bis schwerem COVID-19-Verlauf (TLC 78-102 % des Soll, DLCO 61-81 % des Soll 4 Monate nach einer COVID-19-Erkrankung; [24]). Die lungenfunktionellen Befunde korrelieren mit der Schwere des initialen Verlaufs und bessern sich im Lauf der Zeit, wobei insbesondere die Einschränkung der DLCO über einen längeren Beobachtungszeitraum bis zu einem Jahr persistieren kann [3,11,16,18,32,34]. Bei Patienten nach sehr schwerem COVID-19-Verlauf zeigten sich im 2-Jahres-Verlauf signifikant häufiger Zeichen einer restriktiven Ventilationsstörung und Lungendiffusionsstörung als bei Kontrollpatienten [19] [14].…”
Section: Lungenfunktionelle Befundeunclassified
See 1 more Smart Citation
“…Several long-term longitudinal follow-up cohorts of patients recovered from COVID-19 have shown that although most patients recover well, up to 57.7–100% of patients still have persistent lung structural abnormalities and pulmonary function impairment ( 4 6 ). The common pattern of pulmonary interstitial lesions, also known as post-COVID-19 pulmonary fibrosis or COVID-19 pulmonary fibrosis-like ( 7 ), were ground glass opacities (GGOs), ground-glass attenuation and reticular abnormalities ( 8 ). At the same time, chest imaging showed bilateral diffuse interstitial lung disease among patients who complicated acute respiratory distress syndrome (ARDS) during acute phase ( 9 ).…”
Section: Introductionmentioning
confidence: 99%